(untitled) (Praxis Educativa, 2023)
This article arises from the ongoing research work carried out within the framework of the Doctorate in Educational Sciences, in which we investigate secondary education in the city of Cordoba. On this occasion, we will focus on the processes of educational inclusion in secondary schools, paying particular attention to what we call care practices in the school environment, in two temporalities: before the pandemic and during it. The assumption that guides this work is that the school is an institution of care and that this dimension becomes central in the political and pedagogical discourse in contexts of social, economic or health crises. In this sense, the questions addressed are: What is the relationship between inclusion and care? When and who cares at school? What ways of caring do we register in the school space? What is the pedagogical meaning of care practices?